PENGARUH TEMAN SEBAYA DAN PERSEPSI MEROKOK TERHADAP PERILAKU MEROKOK SISWA SMP KECAMATAN PASAR JAMBI KOTA JAMBI - M. Akmal Ardhi Salsa; M. Ridwan; Muhammad Rifqi Azhary; Puspita Sari (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Smoking behavior among adolescents remains a public health problem that can increase the risk of various diseases in the future. This study aimed to determine the relationship between peer influence and perceptions of smoking and smoking behavior among junior high school students in Pasar District, Jambi. This study was a quantitative study with a cross-sectional design. The sample consisted of 252 junior high school students selected using proportional random sampling. Data collection was conducted using a questionnaire. Data analysis was performed using univariate and bivariate methods using the Chi-Square test with a 95% confidence level. The results showed that of the 252 respondents, 181 respondents (71.8%) had a favorable peer influence category, and 139 respondents (55.2%) had a favorable perception of smoking. The bivariate analysis revealed a significant relationship between peer influence and smoking behavior (p-value = 0.003; PR = 1.33; 95% CI = 1.06–1.67). Furthermore, there was a significant relationship between perceptions of smoking and smoking behavior (p-value = 0.001; PR = 1.32; 95% CI = 1.09–1.61). It can be concluded that peer influence and perceptions of smoking are significantly related to smoking behavior among junior high school students in Pasar District, Jambi.